Impact of the COVID-19 Pandemic on Interventional Cardiology: A Retrospective Study (Community Based Medical Journal, 2025)
The recent COVID-19 outbreak has impacted the delivery of healthcare and interventional cardiology services worldwide. Several studies conducted in different countries have revealed that there was a significant reduction in performing percutaneous coronary intervention (PCI) procedures during the onset of the pandemic; however, the situation of such interventional practice n Bangladesh is not well documented. Hence, this study aims to investigate the changes in the volume of interventional cardiology services before and during the COVID-19 outbreak in a tertiary level healthcare facility of the country. This retrospective study based on record review involved 304 patients admitted into Mugda Medical College Hospital, Dhaka, Bangladesh, between April 2019 and April 2021. The patients were categorized as group A (pre-COVID; N=170) and group-B (COVID; N=134) patients. Data were obtained on patient demographics, risk factors, medical history, type of intervention, and readmission of the patient. The pandemic period had an increased number of patients aged ≥60 years (51.5% vs. 42.9%) and a significant shift in gender distribution (16.4% male vs. 78.2% pre-pandemic). The ST elevation myocardial infarction (STEMI) remains relatively stable between the two groups (60.0% vs. 59.7%; p>0.05). Rates remained stable (40.3% vs. 40.0%; p0.05). An increase in balloon angioplasty procedure was observed during the pandemic (49.41% vs. 62.69%; p